Palynology of late Serpukhovian glacial and postglacial deposits from Paganzo Basin, northwestern Argentina - Perez Loinaze, Valeria Susana (2012)
Palynological analysis is reported here for the first time from glacial and postglacial deposits of the lower-middle section of the Guandacol Formation at the Huaco area, central Paganzo Basin, Argentina. Forty-nine spore species are assigned to twenty-seven genera and twenty-one pollen species are assigned to ten genera, however few acritarchs were identified. Biostratigraphic ranges of species suggest an age no older than late Serpukhovian for the section studied. This age is also supported by radiometric data that indicate an early Bashkirian age at the top of the Guandacol Formation. The palynofloras consist mostly of endemic spore species, and provide new evidence for delimiting the Subzone A of the Raistrickia densa-Convolutispora muriornata Biozone in Argentina. Close correlation is suggested with palynological associations belonging to the widespread glaciation occurred during the Serpukhovian-early Bashkirian in South America and Australia.